2014
DOI: 10.1016/j.ajog.2013.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D regulates contractile profile in human uterine myometrial cells via NF-κB pathway

Abstract: OBJECTIVE Infection triggers inflammation which in turn enhances the expression of contractile associated factors in myometrium and increases the risk of preterm delivery. In this study we assessed vitamin D regulation of inflammatory markers, contractile-associated factors, steroid hormone receptors and NFκB pathway proteins in human uterine myometrial smooth muscle (UtSM) cells cultured in an inflammatory environment. STUDY DESIGN Inflammatory environment was simulated for UtSM cells by co-culturing them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 41 publications
(47 reference statements)
1
44
0
1
Order By: Relevance
“…Cholecalciferol has anti-inflammatory activity because it reduces the production of pro-inflammatory cytokines, such as TNF-a [11]. Also, the 1,25(OH) 2 D 3 reduces the production of IL-1b [37]. Accordingly, in all the treatments cholecalciferol inhibited the gene expression of these cytokines in bMEC.…”
Section: Discussionmentioning
confidence: 94%
“…Cholecalciferol has anti-inflammatory activity because it reduces the production of pro-inflammatory cytokines, such as TNF-a [11]. Also, the 1,25(OH) 2 D 3 reduces the production of IL-1b [37]. Accordingly, in all the treatments cholecalciferol inhibited the gene expression of these cytokines in bMEC.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies reported low vitamin D levels in pregnant women (Dawodu and Wagner 2012; Wagner et al, 2012); however, role of vitamin D in pregnancy outcomes is yet to be fully described. Some studies speculate that given the presence of vitamin D receptors in gestational tissues, there is biological plausibility for variation of vitamin D concentrations during pregnancy (Thota et al, 2014). Interestingly, in the present study, pregnancy status was associated with reduced vitamin D concentrations regardless of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have recently reported that vitamin D deficiency is associated with an increased risk of PTB in African-Americans and Caucasians [10]. Additionally, we have demonstrated that vitamin D elicits anti-inflammatory response, and decreases expression of contractile factors in human uterine smooth muscle cells [11]. Furthermore, specific vitamin D receptor polymorphism has been associated with increased risk of spontaneous idiopathic preterm birth [12].…”
Section: Opinionmentioning
confidence: 99%
“…Among obstetrical societies, ACOG has issued brief committee opinion in July 2011 stating that there is insufficient evidence to recommend vitamin D supplementation for prevention of preterm birth [14]. However, in light of accumulating compelling recent literature [11,13]. Since issuance of that committee opinion, we would encourage reconsideration of evaluating and possibly adapting the Endocrine Society policy (which is co-sponsored by The Institute of Medicine), which could likely have positive impact and may help reduced the persistently high PTB rate and associated high infant mortality rate in this population.…”
Section: Opinionmentioning
confidence: 99%